A Novel Microwave Coaxial Slot Antenna for Liver Tumor Ablation - Acikgoz, H.; Turer, İ. (Advanced Electromagnetics, 2014)
This paper is on the effect of a T-ring shape structure to enhance the capability of a microwave coaxial slot antenna (MCA) in the treatment of liver cancer. The MCA is composed of an interstitial coaxial line that is enclosed in a catheter. The T-ring shape structure is wrapped on the outer conductor of the MCA. Thanks to the new structure, the backward heating problem appearing in many coaxial antennas is reduced and the generated heat in front of the slot is higher than those for a classical MCA.